Is there creatine in plants? The true compound behind the 1H NMR signal at 3.05 ppm in plant extracts - Novais, Leice Milla Ribeiro de; Ali, Sher; D’Oca, Caroline Da Ros Montes; Salome, Kahlil Schwanka; Barison, Andersson (Frontiers in Natural Products, 2024)
Introduction: Some papers describe the presence of creatine in plants, based on a singlet signal at 3.02-3.05 ppm in the 1 H NMR spectra. Although is there creatine in plants? Therefore, to answer this question, a comprehensive NMR investigation has been performed aiming the unambiguous assignment of the compound responsible for that signal.Objective: Determine whether the compound behind the signal at 3.05 ppm is truly creatine or if it was just a misassignment, instead.Methods: Samples of leaves and cherries from Eugenia uniflora in their natural swollen state were submitted to HR-MAS NMR analysis.Results: It was found that the signal at 3.05 ppm was misassigned to creatine. The exhaustive NMR investigation revealed that the signal is related to the amino acid 4-hydroxy-N-methyl proline, instead.The comprehensive NMR investigation revealed that there is no creatine in plants, it was just a misassignment.